Antibiotics release by hybrid bone scaffold: relationship between kinetic profiles and scaffold intrinsic features - Tavoni, Marta; Pupilli, Federico; Restivo, Elisa; Grillini, Laura; Galassi, Elisabetta; Tampieri, Anna; Sprio, Simone (Frontiers in Bioengineering and Biotechnology, 2025)
Bone infections are a major complication in the treatment of bone defects, often leading to chronic conditions such as osteomyelitis and prosthetic joint infections, predominantly caused by Staphylococcus aureus bacteria. Whilst antibiotics are essential to infection control, systemic administration often fails to achieve effective concentrations at the infection site, increasing the risk of toxicity and antimicrobial resistance. In this study we propose a hybrid, scaffold obtained by a bio-inspired mineralization process (HS), designed to support bone healing and enabling localized antibiotic delivery. The HS consist of nanocrystalline magnesium-doped apatite nanocrystals heterogeneously nucleated on self-assembling collagen fibrils, mimicking natural bone mineralization processes. The scaffold is subsequently tested for its ability to modulate the release of vancomycin, gentamicin, and tobramycin and evaluate their efficacy in inhibiting Staphylococcus aureus growth by agar diffusion test. Antibiotic loading using clinically applicable methods and tracking their release over time was inspected and the experimental data was analysed using pseudo-first and pseudo-second order kinetics, showing pathways related to HS chemistry, structure, and drug physicochemical properties. Compared to burst antibiotic releases observed in sintered apatite scaffold, the hybrid scaffold demonstrated a more controlled and sustained release of antibiotics. Our findings highlight how scaffold nanostructure and surface characteristics can influence drug release, with regenerative capacity and sustained local antibiotic delivery potentially improving bone repair by reducing post-surgical infections.